2002
DOI: 10.1523/jneurosci.22-18-07959.2002
|View full text |Cite
|
Sign up to set email alerts
|

Intron 1 Is Required for Cell Type-Specific, But Not Injury-Responsive, Peripherin Gene Expression

Abstract: The "primitive" neurons of the peripheral nervous system (PNS) have the remarkable ability to regenerate new fibers. This regenerative process requires a sequence of gene activation and repression that is poorly understood. One gene that is almost exclusively expressed in neurons of the PNS and is activated after nerve injury is the peripherin intermediate filament gene, but little is known about the genomic elements that control either its restricted expression or its response to nerve injury in adult mice. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Furthermore, it was observed that one of the target DEGs of SP1 was RAB27A , which is involved in the injury response, suggesting its role in the regulation of injury-associated DEGs after SCI. This agrees with the finding that SP1 or SP1-associated proteins are involved in regulating the expression of peripherin intermediate filament gene, which is activated after nerve injury via binding to the intron 1 site ( 37 ). Thus, whether SP1 functions in the same way in regulating injury-associated genes after SCI should be further validated.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it was observed that one of the target DEGs of SP1 was RAB27A , which is involved in the injury response, suggesting its role in the regulation of injury-associated DEGs after SCI. This agrees with the finding that SP1 or SP1-associated proteins are involved in regulating the expression of peripherin intermediate filament gene, which is activated after nerve injury via binding to the intron 1 site ( 37 ). Thus, whether SP1 functions in the same way in regulating injury-associated genes after SCI should be further validated.…”
Section: Discussionsupporting
confidence: 91%
“…It was previously established that the 5Ј-flanking sequences of some nerve injury-associated genes such as GAP43, peripherin, and tubulin-␣, have injury-responsive characteristics (2)(3)(4)(5). However, both the detailed transcriptional machinery and the injury-responsive element within those promoters, which are pivotal for the appropriate gene responses to neuronal injury, have not been clarified.…”
mentioning
confidence: 99%
“…Previous reports have suggested that neuron-specific promoter activity is actualized by neuronal enhancers located upstream of the core promoter, and by non-neuronal repressors within the first intron (Uveges et al 2002, Zhou et al 2005, Kouzmenko et al 1997).…”
Section: Discussionmentioning
confidence: 98%